Specifics of epilepsy treatment during the first year of life in preterm infants and extremely preterm neonates - I. V. Makedonska (Zaporožskij Medicinskij Žurnal)
One of the most important tasks of the modern medical science is neonatal life and health preservation. Achievements in the areas of obstetrical and neonatal assistance have significantly increased the survival rate among extremely preterm neonates at birth. However, monitoring of these children has showed a high level of disability which in the future during the first year of life is often combined with a high morbidity rate and functional disorders.